Testing a model of customer service and satisfaction of a luxury wingshooting lodge experience - Franks, Todd, author; Bright, Alan, advisor; Kang, Soo, committee member; O'Leary, Joseph, committee member; Teel, Tara, committee member (Colorado State University. Libraries, 2023)
This paper explores the application of a customer service and satisfaction model from the outdoor recreation industry to a luxury wingshooting destination. Specifically, it investigates the possibility that domain-level satisfaction will mediate the specific relationship between customer service components and the guests' overall satisfaction with the luxury hunting lodge experience. Data were collected via quantitative self-administered surveys (n=525 completed surveys) that measured three levels of visitor satisfaction (26 individual service items, three service domains, and overall satisfaction), which were administered to guests at a luxury wingshooting destination over four South Dakota pheasant preserve hunting seasons (2017 - 2020) which run from September 1 until March 31 of the following year. This research tested the extent to which satisfaction across three domains (hunting, customer service, & facilities) mediated the influence of 26 individual service items in predicting overall satisfaction with the luxury hunting lodge experience. The 26 service items represented certain areas of satisfaction (domains), and the mediation analysis was limited to those specific domains. Results indicated that satisfaction with each of the three domains partially mediated the relationship between overall satisfaction with the luxury hunting lodge experience and the individual service items. Next, I combined all of the significant individual service items and their three satisfaction domains into one single regression model, with overall satisfaction with the luxury hunting lodge experience as the dependent variable. Of the ten significant service items and three service domains, only five variables proved to be significant, accounting for 76.8% of the explained variance in overall satisfaction with the luxury hunting lodge experience.